Infix of The Dengka Dialect in The Rote Language: A Generative Morphology Approach - Loe, Efron Yohanis; Sutjiati Beratha, Ni Luh; Darma Laksana, I Ketut; Pastika, I Wayan (e-Journal of Linguistics, 2018)
Dengka Dialect is one of the eighteen dialects of Rote language. It is spoken in Northwest Sub distric, Rote Ndao Regency, Nusa Tenggara Province. The eighteen variation sub dialects are Termanu, Korbaffo, Landu, Ringgoú, Upao, Bilba, Diu, L?lenuk, Bokai, Tala?, Keka, Ba?, Lelain, D?ngka, Unal?, Déla, Ti dan Lål?t (Lål?). This research aims at discovering the infixation process in the Dengka dialect of the Rote language.   The applied theoritical approach is generative morphology that is suggested by Aronoff in his article, Word-Based Morphology (1979). According to the rules of morphological process in the Dengka Dialect of the Rote Language, a new theory as the main theory is applied to analyse data findings.   The research method used is descriptive qualitative method. The data are obtained by using observation methods and its techniques, and interlocution method and its techniques. The collected data are writings and voice-recordings. The writings are the main data, which are translations of the Book of Mark in the New Testament, the Story of Easter and the Parable about a Farmer, in the version of Dengka Dialect in the Rote Language. The voice recordings are supporting data, which are obtained from informants by interviewing and recording.   A research finding in Dengka Dialect is infixation. Infix is found in adjective, it is processed by repeating the second syllabe of lexeme base and to produce new words. There are two types of infixation in BRDD, namely 1) infixation by repeating second syllabe of lexeme base without increment of glottal phoneme /?/, and 2) infixation by repeating second syllabe of lexeme base and the increment of glottal phoneme /?/. It process unsuport the grammatical function because it can change the word class of lexeme base but it can change the meaning of lexeme base. The grammatical of infixation is comparative ‘a little bit’.     Keywords : Infix, Rote Language, Dengak Dialect.